The Effectiveness of the Discovery Learning Model Assisted by Video Games to Improve Student Learning Outcomes on the Concept of Momentum and Impulse in High School - Mohamad Nurkhojin; Abdul Haris Odja; Trisnawaty Junus Buhungo; Mursalin Mursalin; Ritin Uloli; Citron S Payu (Faculty of Science and Education, UIN Walisongo Semarang, 2022)
This study aims to determine the effectiveness of the discovery learning model with the help of video games on student learning outcomes on the concept of momentum and impulse in high school. This research is using an experimental method. The research design used was a pretest-posttest control group design. In this study there was an experimental group and a control group. Data collection using essay test and multiple choice tests. Data analysis using the mean difference analysis and N-Gain. The results showed that the t-value on the multiple-choice test was 2.183 and on the essay test was 2.811, which was greater than t-table 2.037. Referring to the rule of testing the hypothesis that if tcount ttable, then H0 is rejected, H1 is accepted, which means there is a significant influence. So it can be concluded that learning using the discovery learning model with the help of video games has a significant effect on student learning outcomes on the concept of momentum and impulse in high school. Through the n-gain test on the multiple choice test it can be seen that the N-gain value for the experimental class is 0.713 and the control class is 0.582. While on the essay test for the experimental class 0.777 and 0.667 for the control class. So it can be concluded that the increase in student learning outcomes using the discovery learning model with the help of video games is higher than the use of the discovery learning model on the concept of momentum and impulse in high school.